An Overview Of Youth and Violence (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2008)
In this paper, an overview of four key questions are addressed: 1) Are todays youth really more violent? 2) How many youth are victims of violence or committing violent acts themselves? 3) What are the major causes of youth violence? and 4) What is known about the prevention and control of youth violence?